A new species of Protium (Burseraceae) from the Pacific Coast of Costa Rica - de Oliveira Perdiz, Ricardo; Daly, Douglas C.; Vicentini, Alberto; Fine, Paul V.a. (Phytotaxa, 2020)
Protium santamariae is described and illustrated. The new species is restricted to the Pacific Coast of Costa Rica but shares morphological similarities with two South American species, P. kleinii and P. krukoffii. We provide a description, a distribution map, notes on its taxonomy, and a key to distinguish it from morphologically similar species.